2012
DOI: 10.1016/j.jpeds.2011.07.041
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Extremely Low Birth Weight Infants Who Received Delivery Room Cardiopulmonary Resuscitation

Abstract: Objective To determine whether delivery room cardiopulmonary resuscitation (DR-CPR) independently predicts morbidities and neurodevelopmental impairment (NI) in extremely low birth weight (ELBW) infants. Study design Cohort study of infants born with birth weight (BW) 401-1000g and gestational age (GA) 23-30wks. DR-CPR was defined as chest compressions and/or drugs. Logistic regression was used to determine associations between DR-CPR and morbidities, mortality and NI at 18-24 months (Bayley II mental or psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
84
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(88 citation statements)
references
References 26 publications
1
84
2
1
Order By: Relevance
“…Asphyxia also impairs cerebral autoregulation, so the brain cannot maintain cerebral blood flow at a near steady state, leaving the brain more vulnerable to cardiovascular hemodynamic instability and hemorrhagic injury (32,33). Therefore, these rapid fluctuations to cerebral blood flow may partially explain why infants given cardiopulmonary resuscitation have poor neurological outcomes and increased risk of developing grade 3 or 4 intraventricular hemorrhages (34).…”
Section: Discussionmentioning
confidence: 99%
“…Asphyxia also impairs cerebral autoregulation, so the brain cannot maintain cerebral blood flow at a near steady state, leaving the brain more vulnerable to cardiovascular hemodynamic instability and hemorrhagic injury (32,33). Therefore, these rapid fluctuations to cerebral blood flow may partially explain why infants given cardiopulmonary resuscitation have poor neurological outcomes and increased risk of developing grade 3 or 4 intraventricular hemorrhages (34).…”
Section: Discussionmentioning
confidence: 99%
“…Heart rate before the commencement of CC was also comparable between groups 53 (15-62) bpm in the 3:1 group versus 42 (15-49) bpm in the SI group, respectively (P=0.490). Table 1 represents values of pH, pco 2 , lactate, and hemoglobin at the start of CPR (end of asphyxia), and the values of pH, pco 2 , and lactate after reestablishment of ROSC, as well.…”
Section: Resultsmentioning
confidence: 99%
“…A lthough chest compressions (CCs) are an infrequent event in newly born infants (≈0.08% for near-term and term deliveries), 1,2 outcome studies of delivery room resuscitations have reported high rates of mortality and neurodevelopmental impairment in those infants receiving CC or epinephrine. 1,2 The poor prognosis associated with receiving cardiac compressions alone or with medications in the delivery room raises questions as to whether improved cardiopulmonary resuscitation (CPR) methods specifically tailored to the newborn could improve outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In children between one and and 8 years old and in adults, the compression must be performed with the hypothenar region of one hand on the sternum, with compression 5 cm deep 12 .…”
Section: () the Sudden Loss Or Interruption Of The Cardiovascular mentioning
confidence: 99%